CFTR/ENaC-dependent regulation of membrane potential during human sperm capacitation is initiated by bicarbonate uptake through NBC - Puga Molina, Lis del Carmen (2018)
To fertilize an egg, sperm must reside in the female reproductive tract to undergo several maturational changes that are collectively referred to as capacitation. From a molecular point of view, the HCO3-dependent activation of the atypical soluble adenylyl cyclase (ADCY10) is one of the first events that occurs during capacitation and leads to the subsequent cAMP-dependent activation of protein kinase A (PKA). Capacitation is also accompanied by hyperpolarization of the sperm plasma membrane. We previously reported that PKA activation is necessary for CFTR (cystic fibrosis transmembrane conductance regulator channel) activity and for the modulation of membrane potential (Em). However, the main HCO3 transporters involved in the initial transport and the PKA-dependent Em changes are not well known nor characterized. Here, we analyzed how the activity of CFTR regulates Em during capacitation and examined its relationship with an electrogenic Na/HCO3 cotransporter (NBC) and epithelial Na channels (ENaCs). We observed that inhibition of both CFTR and NBC decreased HCO3 influx, resulting in lower PKA activity, and that events downstream of the cAMP activation of PKA are essential for the regulation of Em. Addition of a permeable cAMP analog partially rescued the inhibitory effects caused by these inhibitors. HCO3 also produced a rapid membrane hyperpolarization mediated by ENaC channels, which contribute to the regulation of Em during capacitation. Altogether, we demonstrate for the first time, that NBC cotransporters and ENaC channels are essential in the CFTR-dependent activation of the cAMP/PKA signaling pathway and Em regulation during human sperm capacitation.